PT Agrodana Futures Marketing Strategy in Educating People Who Have Experienced Trading Losses: Strategi Pemasaran PT Agrodana Futures Dalam Mengedukasi Masyarakat Yang Pernah Rugi Trading - Hirzy Attirafi; Arief Budiman (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Futures trading is defined as everything related to buying and selling commodities with margin withdrawal and settlement based on Futures Contracts, Sharia Derivative Contracts, and/or other Derivative Contracts, according to Article 1 of Law no. 10 of 2011 concerning Amendments to Law Number 32 of 1997 concerning Commodity Futures Trading. This activity was carried out to explain marketing strategies that can be implemented by PT Agrodana Futures in educating potential customers who have experienced losses in trading. Activities were carried out using the qualitative case study method with interview techniques, observation and document analysis. The results of the activities are presented to partners. The results of the analysis show that effective marketing strategies in educating the public include: (1) Providing educational materials that are easy to access and understand, (2) consulting with trading experts, (3) using successful customer testimonials as proof of credibility, and (4) offering trading demo program to increase people's self-confidence.